HER2-positive breast cancer with brain metastasis, long responder to lapatinib therapy - Chiara Saggia (AboutOpen, 2018)
We report the case of a 45-year-old patient diagnosed, after four years from the initial diagnosis of infiltrating ductal carcinoma, with lymph node, hepatic, pulmonary and bone diseases deriving from HER2-positive breast cancer. While the association docetaxel + trastuzumab led to a partial response in all locations, trastuzumab maintenance treatment was witheld due to multiple brain progression. After neurosurgical surgery and panencephalic radiotherapy, the patient started a lapatinib-based therapy with partial response in all disease sites and minimal brain progression. The peculiarity of this clinical case is the long survival of a patient in excellent clinical condition and with good quality of life, even in the presence of HER2-positive diffuse brain disease. The patient, thanks to combined treatments and target therapy with lapatinib, reached a 3-year progression-free interval, despite the early brain progression during trastuzumab and a 6-year survival interval from the diagnosis of brain metastases. These data support lapatinib as an active therapeutic choice, effective and well tolerated also in the long term, in early progressing patients treated with trastuzumab, despite the presence of brain metastases (Oncology).